2007
DOI: 10.2337/dc06-2444
|View full text |Cite
|
Sign up to set email alerts
|

Costs of a Self-Selected, Health-Promoting Diet Among the Participants of the Finnish Diabetes Prevention Study

Abstract: Several studies have shown that lifestyle changes including weight reduction, increased physical activity, and dietary modification are effective in preventing the development of type 2 diabetes (1-4). However, various barriers are known to interfere with the adoption of a healthier lifestyle. One such barrier is diet costs (5). A few studies have explored the relationship between the quality and costs of diets (6 -13), and the results are conflicting. Observational studies (6 -10) suggest that a healthy diet … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
21
0

Year Published

2007
2007
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(23 citation statements)
references
References 14 publications
2
21
0
Order By: Relevance
“…Previous support for a positive association of diet quality and cost has come from cross-sectional research, much of which assesses energy cost rather than daily diet cost, and for which the overall effect attributable to diet quality is small 20 . Only a small body of intervention research has examined the effect on cost of changes in diet quality 3235 ; these studies and the current analysis all find no increase in diet cost in association with improved diet quality. Additionally, we observed an inverse association of change in diet cost with change in WPFD among parents.…”
Section: Discussionmentioning
confidence: 47%
See 1 more Smart Citation
“…Previous support for a positive association of diet quality and cost has come from cross-sectional research, much of which assesses energy cost rather than daily diet cost, and for which the overall effect attributable to diet quality is small 20 . Only a small body of intervention research has examined the effect on cost of changes in diet quality 3235 ; these studies and the current analysis all find no increase in diet cost in association with improved diet quality. Additionally, we observed an inverse association of change in diet cost with change in WPFD among parents.…”
Section: Discussionmentioning
confidence: 47%
“…Diet cost was estimated using methods consistent with previous research 3235 . Price information from two online national supermarkets common to the study location was recorded and averaged for each food component reported (approximately 1600 items), except that prices for items reported from a named store or restaurant were obtained from these retail outlets.…”
Section: Methodsmentioning
confidence: 99%
“…Finally, several (35)(36)(37)(38)(39) although not all (40) intervention studies have reported that nutrient-dense diets consumed as a result of nutrition interventions were not more expensive than lower-quality diets. These intervention studies provided individual instructions on how to identify nutritious low-cost foods, how and where to make food purchases, and how to store and prepare the foods, possibly facilitating the consumption of a healthier diet at lower cost.…”
Section: Discussionmentioning
confidence: 99%
“…216 Dietary fibre and fat contents were strong predictors of success, even after adjustment for weight loss. 213 Results: primary outcomes Progression to diabetes Tuomilehto et al (2001) 183 assessed the incidence of T2DM (WHO 1985 criteria) by annual oral glucose tolerance testing for up to 6 years (mean follow-up 3.2 years).…”
Section: Interventionmentioning
confidence: 95%
“…[205][206][207][208][209][210][211][212][213][214][215][216][217][218][219] Description and quality of trial This RCT of 523 participants with IGT in Finland compared intensive lifestyle intervention with a control group. Participants were recruited by screening high-risk individuals (e.g.…”
Section: The Finnish Diabetes Prevention Studymentioning
confidence: 99%